The use of psychological and psychiatric methods in determining valeological competence formation in non-medical students of Ukraine - Shevchenko, A. S.; Tolstaia, T. Yu.; Shtefan, L. V.; Shevchenko, V. V.; Kucherenko, S. M.; Kucherenko, N. S. (Харківський національний медичний університет, 2023)
Background. Valeological competence is the ability to lead a healthy lifestyle. Teaching the basics of a healthy lifestyle in higher education institutions of Ukraine is regulated by higher education standards. Valeological competence is formed in non-medical students during the teaching of valeological disciplines. At the Ukrainian Engineering Pedagogics Academy (Kharkiv) such a valeological discipline is "Health Pedagogy", at the National Technical Univer-sity "Kharkiv Polytechnic Institute" (Kharkiv) and at the National University of Civil Defense of Ukraine (Kharkiv) – "Fundamentals of Medical Knowledge and Health-Saving". Confidential questionnaires are used to assess the success of the formation of the motivational-value and per-sonal components of valeological competence, the list of questions of which allows studying the behavior patterns of non-medical students. Aim. To establish the conformity of the questions of the questionnaires, which are used to study the formation of the motivational-value and personal components of the valeological com-petence in non-medical students, to the existing psychological and psychiatric methods. Materials and Methods. The bibliosemantic method and the system analysis method were used in the study. Results. Correspondence was established between the questions used to assess the success of the formation of the motivational, value and personal components of valeological competence, with the questions of such psychological and psychiatric methods questionnaires by Rogers K. and Diamond R. (social-psychological adaptation), Boyko V.V. (level of emotional burnout), Burtyanskyi D.L. and Krystal V.V. (levels of socio-pedagogical and sexual-behavioral adaptation of a married couple or sexual partners), Navran L. (satisfaction with married life or life with a sexual partner) and the CAGE-AID screening test for alcohol and/or drug addiction. Conclusions. The questions of the questionnaires used for assess the success of the formation of the motivational-value and personal components of valeological competence in non-medical students, correspond to existing psychological and psychiatric methods, the modification of which to the needs of assessing the formation of the components of valeological competence requires further research.
Keywords: qualitative factor-criterion model; health-saving; valeological education